The Effects of Momentum Trading, Market Volatility, and Liquidity on the Risk of Sharia Stock Portfolios in Indonesia - Tyas Indrayanti; Andini Bandiah; Tsinta Aryaningtyas; Isnani Fauziah; Bagas Saputra; Maria Pandin (Indonesian Journal Publisher, 2025)
This study aims to analyze the effect of momentum trading, market volatility, and liquidity on the risk of sharia stock portfolios at Islamic banks in Indonesia. The research population consists of four Islamic banks listed on the Indonesia Stock Exchange (BANK, BRIS, BTPS, and PNBS) during the period 2022–2024. Data were obtained from the official website of the Indonesia Stock Exchange and processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS 4 application. The independent variables used were momentum trading (RSI, MACD, Stochastic Oscillator), market volatility (ATR and Bollinger Bandwidth), and liquidity (Turnover Ratio and Bid-Ask Spread), while the dependent variables were sharia stock portfolio risk (Beta and Standard Deviation). The results of the study indicate that momentum trading and market volatility have a positive and significant effect on the risk of sharia stock portfolios, while liquidity has no significant effect. Simultaneously, all three variables have a significant effect on portfolio risk with an R² value of 0.829. These findings indicate that market volatility is the dominant factor affecting the risk of sharia stock portfolios in Indonesia. The implication of this study is that investors need to pay attention to technical indicators such as momentum and volatility to minimize investment risk, while Islamic capital market managers are advised to improve literacy and transparency so that investment strategies are more oriented towards fundamentals and Islamic principles.